Taiwanin E Induces Cell Cycle Arrest and Apoptosis in Arecoline/4-NQO-Induced Oral Cancer Cells Through Modulation of the ERK Signaling Pathway - Wang, Shih-Hao; Wu, Hsi-Chin; Badrealam, Khan Farheen; Kuo, Yueh-Hsiung; Chao, Yun-Peng; Hsu, Hsi-Hsien; Bau, Da-Tian; Viswanadha, Vijaya Padma; Chen, Yi-Hui; Lio, Pei-Jei; Chiang, Chung-Jen; Huang, Chih-Yang (Frontiers in Oncology, 2019)
Taiwanin E is a bioactive compound extracted from Taiwania cryptomerioides Hayata. In this research endeavor, we studied the anti-cancer effect of Taiwanin E against arecoline and 4-nitroquinoline-1-oxide-induced oral squamous cancer cells (OSCC), and elucidated the underlying intricacies. OSCC were treated with Taiwanin E and analyzed through MTT assay, Flow cytometry, TUNEL assay, and Western blotting for their efficacy against OSCC. Interestingly, it was found that Taiwanin E significantly attenuated the cell viability of oral cancer cells (T28); however, no significant cytotoxic effects were found for normal oral cells (N28). Further, Flow cytometry analysis showed that Taiwanin E induced G1cell cycle arrest in T28 oral cancer cells and Western blot analysis suggested that Taiwanin E considerably downregulated cell cycle regulatory proteins and activated p53, p21, and p27 proteins. Further, TUNEL and Western blot studies instigated that it induced cellular apoptosis and attenuated the p-PI3K/p-Akt survival mechanism in T28 oral cancer cells seemingly through modulation of the ERK signaling cascade. Collectively, the present study highlights the prospective therapeutic efficacy of Taiwanin E against arecoline and 4-nitroquinoline-1-oxide-induced oral cancer.